iPSC-based approach for human hair follicle regeneration - Vatanashevanopakorn, Chinnavuth; Sartyoungkul, Thanutchaporn (Frontiers in Cell and Developmental Biology, 2023)
Hair follicles (HFs) are a multifunctional structure involved in physical protection, thermoregulation, sensational detection, and wound healing. Formation and cycling of HFs require dynamic interaction between different cell types of the follicles. Although the processes have been well studied, the generation of human functional HFs with a normal cycling pattern for clinical utilization has yet to be achieved. Recently, human pluripotent stem cells (hPSCs) serve as an unlimited cell source for generating various types of cells including cells of the HFs. In this review, HF morphogenesis and cycling, different cell sources used for HF regeneration, and potential strategies for HF bioengineering using induced pluripotent stem cells (iPSCs) are depicted. Challenges and perspectives toward the therapeutic use of bioengineered HFs for hair loss disorder are also discussed.